Geochemistry of the Lake Sediments on Robert Island, South Shetland Islands, Antarctica: implications for weathering processes in Polar areas - ÖZYURT, MERVE; DEMİR, YILMAZ; Özkan, Korhan; KANDEMİR, RAİF (Turkish Journal of Earth Sciences, 2023)
The preliminary results of geochemical analyses of the surface sediments from 4 lakes on Robert Island, South Shetland, Antarctica, are presented herein. The samples were collected during the Turkish Antarctic Expedition (TAE-II) in 2018. Sediment samples were obtained from the littoral zone (approximately 20 cm) of 4 different lakes exposed on the glacier-free land area on Robert Island. The lake sediments predominantly consist of fine-grained sand, clay, and silt particles. These particles include Fe-shale and graywacke geochemical characteristics. Their plagioclase index of alteration, chemical index of weathering, chemical index of alteration, and other weathering index values, suggest that the studied sediments have likely undergone low to moderate weathering and alteration processes. The Th/U ratios generally indicated a lower distribution relatively to the upper continental crust, and they displayed slight enrichment in alkali elements, indicating a low degree of chemical weathering that has slightly influenced the sediment chemistry. Moreover, the Gd/Yb, Zr/Y, and La/Yb ratios exhibited similarities with the surrounding volcanic rocks on Robert Island. Additionally, their chondrite-normalized rare earth element (REE) patterns exhibited a similar trend, implying that the REE composition of the sediments is predominantly controlled by the local source rocks. Nevertheless, there were slight differences in the Y/Ho ratios and heavy REE (HREE) contents, suggesting the presence of additional sources contributing to the REE supply in the lake basins. The Co/ Th, La/Sc, Th/Sc, and Zr/Sc ratios mostly resembled those of basic volcanic rocks, while the Rb, K, HREE, and Ni values dominantly indicated basic rocks with a minor input from felsic magmatic or quartzose sedimentary rocks. Considering the geomorphology and location of the basins, which are mostly situated along the coast where foehn winds have a limited influence over ice-free areas, it is likely that locally resuspended materials have had a significant ...